The Riddles of the Fourth Gospel : An Introduction to John - Anderson, Paul N., 1956- (Book collections on Project MUSE., 2011)
"Paul Anderson, a leading scholar of the Fourth Gospel, provides an introductory textbook, crafted for a semester course, which leads students through literary, historical, and theological aspects of the Fourth Gospel's most vexing puzzles. Traditional, historical-critical, and literary-critical approaches are deftly introduced and their limitations evaluated; questions of the Gospel's authorship, composition, relationship to the Synoptics, and origins in particular historical experiences are succinctly addressed; and distinctive Johannine perspectives on Jesus, the church, and the world are discussed"--Publisher description